Soil reinforcement with synthetic and natural fibres: a review - Tuan Ismail, Tuan Noor Hasanah; Yuriz, Yasmin; Yahya, Nur Faezah; Adnan, Suraya Hani; Mat Hassan, Nik Normunira; Wan Jusoh, Wan Amizah; Abdul Rahman, Mohd Fahrni (Penerbit UTHM, 2020)
Problematic soil is a common issue in construction activities, particularly when dealing with peat and clay soils of poor geotechnical properties. Such soils are non-homogeneous, and their properties vary greatly from place to place or, in some cases, even at one place. The growing development demand and insufficient suitable ground have forced the development to use problematic soil. It is therefore important that the soil properties are improved so that any construction thereon is stable and safe. Soil improvement methods are of several different kinds and ways, but the reinforcement of fibre-based approaches have recently gained increasing interest in the field of geotechnical engineering. This technique is currently used in six main areas worldwide, including pavement, road and railway embankment, foundation, slope, and bridge. The main focus of this paper is to examine the feasibility, potential and efficacy of different types of natural and/or synthetic fibres in soil reinforcement by critically reviewing past researches. The pros and cons of natural versus synthetic fibres will also be discussed.